Oracle Certified Professional Java SE 8 programmer exam 1Z0-809 : a comprehensive OCPJP 8 certification guide - Ganesh, S. G.; Kiran, Hari; Sharma, Tushar (Expert's voice in Java., 2016)
This book is a guide for the Java SE 8 Programmer II exam (IZ0-809). It provides 100% coverage of the exam topics, a full-length mock exam, practice exam questions, exam notes and tips and is a comprehensive guide for the OCPJP 8 exam. Exam topics are discussed using numerous programming and real-world examples. Each chapter ends with practice exam questions and a quick summary that revises key concepts covered in the chapter from exam perspective. After reading the main chapters, you can take the full-length mock exam to ensure that you have enough practice before actually taking the exam. If you are an OCPJP 8 exam aspirant, this book is certainly for you. It assumes that you are already familiar with Java fundamentals (that is in line with the prerequisite of having a OCAJP 8 certification before you take up the OCPJP 8 exam). --